CATTLE GRUB: TIME OF FLIGHT OF IMAGO IN THE CONDITIONS OF THE REPUBLIC OF KARAKALPAKSTAN (Scientific journal of the Fergana State University, 2023)
The dates of flight of adults of cattle grub in the southern and northern zones of the Republic of Karakalpakstan have been studied, and on the basis of the studies carried out, the optimal timing of early chemotherapy against larvae of the 1st stage of cattle grub has been recommended